Improve manganese leaching efficiency by adding different complexants during ammonia leaching of low-grade rhodochrosite. (October 2022) - Yang, Peng; Liang, Xiaoping; Wu, Chengbo; Cui, Tengfei; Wang, Yu
Graphical abstract: Highlights: Complexant is added during the ammonia leaching of low-grade rhodochrosite to improve the leaching efficiency of manganese. Manganese leaching efficiency is improved because the complex formed by the complexant and manganese increases the solubility of manganese in the leaching process. EDTA is considered to be the most effective complexant to improve the leaching efficiency of manganese. Abstract: There is a problem of low manganese leaching efficiency in the treatment of high-phosphorus and low-grade rhodochrosite by ammonia leaching. In this work, a proven and effective method was proposed to improve the manganese leaching efficiency by adding complexant during ammonia leaching of high-phosphorus and low-grade rhodochrosite. The thermodynamics of leaching process of rhodochrosite calcine after adding citric acid (CA), ethylenediaminetetraacetic acid (EDTA), nitrilotriacetic acid (NTA), glycine (Gly) different complexants were analyzed, and the effects of complexants on the manganese leaching efficiency were studied experimentally. Thermodynamic analysis and experimental results indicated that the four complexants can improve the leaching efficiency of manganese to varying degrees, and addition the EDTA has the best effect on improving the leaching efficiency of manganese. Moreover, various leaching parameters when EDTA was added and the effect of adding EDTA on ammonia evaporation product were further studied. The leaching optimum technology of rhodochrosite calcine with EDTA was obtained. Under the optimum technology, the manganese leaching efficiency increased to 90.1%. The addition of EDTA in the leaching process did not affect the ammonia evaporation product, and MnCO3 product with 43.26% manganese content were obtained after evaporating ammonia.